INTELLIGENT MANAGEMENT IN HEALTHCARE: LEADERSHIP, INFORMATION TECHNOLOGY, AND INTEGRATION OF THE MULTIPROFESSIONAL TEAM IN THE ORGANIZATION OF CARE - da Costa, Anna Catharinna; Sestari, Larissa Emanuelle; Coelho, Patrícia dos Santos Moutinho; Ferreira, Lauriene Karina Ramos da Costa; Cardoso, Leidson Frank Santana; Facioni, Jeane da Silva; de Oliveira, Alexandre Almeida; Gomes, Monize Lopes de Araújo; Ribeiro, Neide Garcia; Melo, Kárita Roberta da Silva; da Silva, Elizabeth Cristina; Sobral, Iva Zaiza Valente; et al. (Seven Editora, 2026)
Digital transformation has profoundly reshaped the organization of healthcare work and repositioned multiprofessional team management as a central element in improving care quality. The incorporation of information technology, through electronic health records, monitoring systems, and integrated management platforms, has enhanced collaboration among physicians, nurses, physiotherapists, nutritionists, pharmacists, dentists, and healthcare managers, promoting greater integration of clinical practices and strengthening data-driven decision-making. This chapter aimed to analyze the role of information technology in the management of multiprofessional teams, discussing its impacts on care organization, healthcare leadership, and the development of digital competencies in contemporary health systems. This is a qualitative study with a theoretical-analytical approach, grounded in recent scientific literature on digital transformation, healthcare management, and interprofessional practice. The findings indicate that digital systems improve professional communication, enhance care coordination, and foster a more collaborative organizational culture. However, challenges related to professional training, technological governance, and institutional adaptation to change remain evident. It is concluded that intelligent healthcare management, supported by the integration of leadership, information technology, and multiprofessional collaboration, represents a promising pathway toward more efficient, safe, and patient-centered health services.